Technological Sovereignty, Smart Power and Geopolitical Instability - LEON, Gonzalo; DA PONTE, Aureliano (Journal of the Spanish Institute for Strategic Studies, 2022)
The debate on the scope of the concept of technological sovereignty and especially its implications has gained momentum in the context of the European Union (EU) to guarantee the principle of "strategic autonomy" which became a key common political piece to strengthen the bloc's position in the world. However, its political and aspirational nature, although abstract in its concreteness, has not been translated into defined objectives in time, space, and opportunity. The article frames this debate in the conditions of geopolitical instability that pervade international dynamics and discusses the rationality of the notion of 'smart power' as a strategic option for the EU. On this basis, it analyses China's presence in Africa and its possible impact on European strategic autonomy.
Keywords: Technological Sovereignty, Smart Power, European Union, China, Africa